26 Hen. 8, c. 6, § 4 (1534) - (:unkn) unknown (General Publisher, 1534)
Prohibited Welsh residents or lords from bearing any bill, longbow, crossbow, handgun, sword, staff, dagger, halberd, morespike, spear, or any other manner of weapon into sessions, court, town, church, fair, market, other congregation, or on the highways in affray of the King's peace or the King's liege people. Violators punished with imprisonment and fine.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES